(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
The economic development of the Republic of Uzbekistan largely depends on traditional energy sources. Electricity generation is carried out by generation at thermal power plants, which account for 87.3% of the total installed capacity, and at hydroelectric power plants (12.7%). The growth of social tension in the world and the presence of deep-seated environmental problems cause great interest in the use of new energy sources. One of the key issues for solving the economic development of the Republic of Uzbekistan is the transition to "green energy".